Use of allele-specific qPCR and PCR-RFLP analysis for rapid detection of the SARS-CoV-2 variants in Tunisia: A cheap flexible approach adapted for developing countries - Wajdi Ayadi; Fahmi Smaoui; Saba Gargouri; Sana Ferjani; Zaineb Hamzaoui; Awatef Taktak; Amel Chtourou; Houda Skouri-Gargouri; Azza Hadj Sassi; Mouna Ben Sassi; Sameh Trabelsi; Ali Gargouri; et al. (PLoS ONE, 2025)
Monitoring the emergence and propagation of SARS-COV2 variants, especially Omicron variants, remains a major concern in developing countries, including Tunisia. We here report lessons of simple approaches used to track prevalent Omicron variants in the city and district of Sfax, Tunisia, between June 2022 and April 2023. Initially, the screening approach was designed by selecting and verifying key SARS-CoV-2 mutations using publicly available sequencing data. Then, the analytical performance of the screening tests was rigorously assessed before being implemented on 227 confirmed COVID-19 cases. In a first stage, from June to September 2022, allele-specific (AS)-qPCR detection of deletions ΔHV69-70 (S gene) and ΔKSF141-143 (ORF1a gene) allowed identification of BA.5 as the predominant variant (128 out of 165 cases; 77.5%) which quickly replaced the pre-existing lineages BA.4 (15.7%) and BA.2 (6.7%). In a second stage, from October 2022 to April 2023, circulation of additional variants was demonstrated using concomitant detection of new relevant mutations by PCR-RFLP (n=62). Detection of mutations Y264H (ORF1b) and V445P/G446S (S gene) resulted in the identification of 38 cases of the BQ.1 variant and 14 cases of the XBB variant, respectively. Further restriction analysis of the S gene was conducted to screen more recent sublineages, including CH.1.1. For all sequenced cases (n=115), our rapid detection assays showed perfect concordance with sequencing results in identifying SARS-CoV-2 variants. These findings highlight the potential of simple, cheap and proven methods for rapid genotyping and monitoring of SARS-COV2 variants. Therefore, these methods appear as valuable tools for effective infection control and prevention in developing countries.